'Little Ice Age' glacier extent and subsequent retreat in Svalbard archipelago. (September 2017) - Martín-Moreno, Raúl; Allende Álvarez, Fernando; Hagen, Jon Ove
The influence of the 'Little Ice Age' (LIA) on the glaciers of Svalbard has been well documented for a long time. This paper presents new data on the LIA maximum glacier extent and retreat by aerial photo interpretation and Geographic Information Systems (GIS) tools. We also make cartography where all results are shown in greater detail. During the LIA maximum, we find that the glacier area of Svalbard was 38, 871 km 2, and since then, the total glacier area loss in the archipelago has been 5096 km 2 (13.1%). The total current glaciated area from the late 2000s is 33, 775 km 2 . Since the LIA, the glaciers in the main islands of the archipelago have retreated by 12.8% in Spitsbergen, 13.4% in Nordaustlandet, and 16.7% in Barentsøya and Edgeøya. The analysis of the LIA maximum glacier extent in the different major drainage basins shows important differences; about 100 years ago, some glacier basins were more than 19% larger in the western and central regions of Spitsbergen, or even more than 23% larger in southern Nordaustlandet, while other small basins found in the northeast of this island were barely 1% larger. The greatest retreats are found in the tidewater glaciers, more variable and responsive to the water temperature changes, water dynamics, and bathymetry. In addition, the advances at some of these glaciers may correspond with surges, which means that the rapid retreats are caused by the post-surging phases as well as climate. The conclusions of this research point out an important ice loss in all of Svalbard since the LIA and the high vulnerability of this Arctic archipelago to global warming.